URGENSI PEMBAHARUAN REGULASI PERLAKUAN PAJAK PENGHASILAN UNTUK BISNIS KONSTRUKSI KUALIFIKASI USAHA KECIL - Setiadi Alim (Jurnal Bisnis Terapan, 2022)
This research is a type of literature research that aims to examine whether regulations regarding the Income Tax of construction business need to be updated according to various dynamics that occur, including other related regulatory changes. Because there are several arrangements on Income Tax of construction business which tend to be inconsistent and overlapping. The research results indicate that it is necessary to revise the Income Tax regulation for construction services business with several recommendations, namely: (i) the limit for taxpayers who may be subject to Income Tax calculation based on Regulation of The Government Number 23 of 2018 is reduced from Rp.4,800,000,000.00 to Rp.2,500,000,000.00; (ii) the Income Tax Law for construction business in article 23 paragraph (1) letter c. number 2. of the Income Tax Law is abolished, in order to avoid double regulation; (iii) construction business with small qualifications should be subject to Income Tax Law based on Regulation of The Government Number 23 of 2018. Imposition of Income Tax based on Regulation of The Government Number 51 of 2008 which was last amended by Regulation of The Government Number 9 of 2022 only applies to construction business with medium and big qualifications.